Valuing fisheries depreciation in natural resource accounting - Tai, Shzee Yew; Noh, Kusairi Mohd; Abdullah, Nik Mustapha Raja (Springer Science and Business Media LLC, 2000)
In this paper, an approach based on the net present value method is used to account for the changes in the value of fisheries resources. Changes in the value of fisheries resources can occur between successive years' catch as well as between current and optimal levels of catch. These changes need to be accounted for in the national accounting system to reflect the 'true' net national income that is sustainable. The approach outlined in this paper is desirable as it allows the estimation of the depreciation value of fisheries resource with limited biological information. The application of the approach to the pelagic fisheries in Northeast Peninsular Malaysia (NEPM) showed that the resource depreciated in value over most years from 1982 to 1993. These depreciations correspond to increased fishing effort. In addition, pelagic catches in NEPM from 1982 to 1993 were lower than the optimal levels of catch due to overfishing. Thus policies aimed at reducing fishing effort can provide improvement in both the potentially higher capital values of the fishery resource and the earning potentials of the fishing industry in NEPM.